Carbon stocks and accumulation rates in Red Sea seagrass meadows. Issue 1 (December 2018) - Serrano, Oscar; Almahasheer, Hanan; Duarte, Carlos; Irigoien, Xabier
Abstract Seagrasses play an important role in climate change mitigation and adaptation, acting as natural CO2 sinks and buffering the impacts of rising sea level. However, global estimates of organic carbon (Corg ) stocks, accumulation rates and seafloor elevation rates in seagrasses are limited to a few regions, thus potentially biasing global estimates. Here we assessed the extent of soil Corg stocks and accumulation rates in seagrass meadows (Thalassia hemprichii, Enhalus acoroides, Halophila stipulacea, Thalassodendrum ciliatum andHalodule uninervis ) from Saudi Arabia. We estimated that seagrasses store 3.4 ± 0.3 kg Corg m−2 in 1 m-thick soil deposits, accumulated at 6.8 ± 1.7 g Corg m−2 yr−1 over the last 500 to 2, 000 years. The extreme conditions in the Red Sea, such as nutrient limitation reducing seagrass growth rates and high temperature increasing soil respiration rates, may explain their relative low Corg storage compared to temperate meadows. Differences in soil Corg storage among habitats (i.e. location and species composition) are mainly related to the contribution of seagrass detritus to the soil Corg pool, fluxes of Corg from adjacent mangrove and tidal marsh ecosystems into seagrass meadows, and the amount of fine sediment particles. Seagrasses sequester annually around 0.8% of CO2 emissions from fossil-fuels by Saudi Arabia, while buffering the impacts of sea level rise. This study contributes data from understudied regions to a growing dataset on seagrass carbon stocks and sequestration rates and further evidences that even small seagrass species store Corg in coastal areas.